Supervision Across the Career: Perceptions and Experiences of Highly Regarded Trainees and Practicing Therapists - Sandra E. Stewart; Janette G. Simmonds (Psychotherapy and Counselling Journal of Australia)
Perceptions and experiences of supervision were investigated across 23 psychotherapists’ careers from training, through mid-career to senior using a cross-sectional design within an exploratory, qualitative paradigm. Promising beginners and highly regarded mid-career and senior therapists were recruited according to literature-derived criteria for therapeutic expertise. Six beginners, six mid-career, and eleven senior therapists were interviewed about their reasons for becoming and remaining a therapist, their past and current practice, and perceived developmental influences. Supervision was identified as the most valued developmental influence. Interview transcript excerpts coded as pertaining to supervision were subject to inductive content analysis, followed by thematic analysis. Participants reported being highly interconnected and influenced by supervisory relationships, with some relationships spanning decades. This research provides a career-span perspective and contributes to the literature about post-training supervision. Findings offer practice implications for both practitioners and supervisors wishing to optimise the supervision experience.